Theoretical and Experimental Studies on Novel High-Gain Seeded Free-Electron Laser Schemes - Feng, Chao.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This dissertation focuses on the study of novel high-gain free-electron laser (FEL) operation schemes with external seed lasers. The technique of manipulating the phase space of the electron beam, which is widely used in novel seeded FEL schemes, is systematically studied. Several novel FEL schemes are proposed for the generation of intense coherent FEL pulses with short wavelength, sub-femtosecond pulse length or multiple carrier frequency properties, which meet the needs of FEL users. Results of experiments are described for the recently proposed FEL schemes such as echo-enabled harmonic generation and cascaded high-gain harmonic generation. New photon/electron beam diagnostic methods are also developed for these experiments and future high-gain FEL facilities.
Introduction -- Basic theory of free-electron laser -- Theoretical studies for novel high-gain FEL schemes -- Experimental studies for novel high-gain FEL schemes -- Conclusions and prospects.
Keywords: Physics; Particle acceleration; Lasers; Photonics; Physical measurements; Measurement; Physics; Laser Technology, Photonics; Particle Acceleration and Detection, Beam Physics; Measurement Science and Instrumentation; Electronic books